THE EFFECTIVENESS OF MAKING VIDEO TUTORIALS IN IMPROVING STRENGTHENING LURING LEARNING IN VOCATIONAL HIGH SCHOOL OF GELORA PANCASILA PENGAJAHAN IN ACADEMIC YEAR 2020/2021 - Akmalia, Rizki; Suhartono, Budi (Universitas Dharmawangsa Medan, 2021)
This research is for: 1) to determine the effectiveness of making video tutorials at SMK Gelora Pancasila Pengajahan TA 2020/2021, 2) to determine the enhancement of offline learning at SMK Gelora Pancasila Pengajahan TA. 2020/2021. This type of research is field research (field research) because naturalistic research is carried out in natural conditions (natural setting). The results of this study are: 1) The effectiveness of making video tutorials to support student learning in schools has actually increased from the previous teacher only 1 person made learning videos, but with the appeal and encouragement given there was a fairly good increase, namely there were 13 teachers in the field of study who trying to make video tutorials to support learning. 2) Increasing the strengthening of offline learning at SMK Gelora Pancasila has been helped by the existence of video tutorials made by teachers in one school channel with all fields of study in SMK which shows 85% student success.